Preexisting coronary heart disease and susceptibility to long-term effects of traffic-related air pollution: A matched cohort analysis. (13th May 2020) - Cohen, Gali; Steinberg, David M; Keinan-Boker, Lital; Yuval,; Levy, Ilan; Chen, Shimon; Shafran-Nathan, Rakefet; Levin, Noam; Shimony, Tal; Witberg, Guy; Bental, Tamir; Shohat, Tamar; et al.
Abstract: Background: Individuals with coronary heart disease are considered susceptible to traffic-related air pollution exposure. Yet, cohort-based evidence on whether preexisting coronary heart disease modifies the association of traffic-related air pollution with health outcomes is lacking. Aim: Using data of four Israeli cohorts, we compared associations of traffic-related air pollution with mortality and cancer between coronary heart disease patients and matched controls from the general population. Methods: Subjects hospitalized with acute coronary syndrome from two patient cohorts (inception years: 1992–1993 and 2006–2014) were age- and sex-matched to coronary heart disease-free participants of two cycles of the Israeli National Health and Nutrition Surveys (inception years: 1999–2001 and 2005–2006). Ambient concentrations of nitrogen oxides at the residential place served as a proxy for traffic-related air pollution exposure across all cohorts, based on a high-resolution national land use regression model (50 m). Data on all-cause mortality (last update: 2018) and cancer incidence (last update: 2016) were retrieved from national registries. Cox-derived stratum-specific hazard ratios with 95% confidence intervals were calculated, adjusted for harmonized covariates across cohorts, including age, sex, ethnicity, neighborhood socioeconomic status, smoking, diabetes, hypertension, prior stroke and prior malignancy (the latter only in the mortality analysis). Effect-modification was examined by testing nitrogen oxides-by-coronary heart disease interaction term in the entire matched cohort. Results: The cohort (mean (standard deviation) age 61.5 (14) years; 44% women) included 2393 matched pairs, among them 2040 were cancer-free at baseline. During a median (25th–75th percentiles) follow-up of 13 (10–19) and 11 (7–17) years, 1458 deaths and 536 new cancer cases were identified, respectively. In multivariable-adjusted models, a 10-parts per billion nitrogen oxides increment was positively associated with all-cause mortality among coronary heart disease patients (hazard ratio = 1.13, 95% confidence interval 1.05–1.22), but not among controls (hazard ratio = 1.00, 0.93–1.08) ( p interaction  = 0.003). A similar pattern was seen for all-cancer incidence (hazard ratioCHD  = 1.19 (1.03–1.37), hazard ratioCHD-Free  = 0.93 (0.84–1.04) ( p interaction  = 0.01)). Associations were robust to multiple sensitivity analyses. Conclusions: Coronary heart disease patients might be at increased risk for traffic-related air pollution-associated mortality and cancer, irrespective of their age and sex. Patients and clinicians should be more aware of the adverse health effects on coronary heart disease patients of chronic exposure to vehicle emissions.